Experimental Analysis of Bragg Reflection Peak Splitting in Gratings Fabricated Using a Multiple Order Phase Mask - Statkiewicz-Barabach, Gabriela (Sensors (Basel), 2019)
We performed an experimental analysis of the effect of phase mask alignment on the Bragg grating reflection spectra around the wavelength of λ(B) = 1560 nm fabricated in polymer optical fiber by using a multiple order phase mask. We monitored the evolution of the reflection spectra for different values of the angle ϕ by describing the tilt between the phase mask and the fiber. We observed that the peak at λ(B) is split into five separate peaks for the nonzero tilt and that separation of the peaks increases linearly with ϕ. Through comparison with theoretical data we were able to identify the five peaks as products of different grating periodicities, which are associated with the interference of different pairs of diffraction orders on the phase mask.